Reperfusion therapies and in-hospital outcomes for ST-elevation myocardial infarction in Europe: the ACVC-EAPCI EORP STEMI Registry of the European Society of Cardiology. (14th August 2021) - Zeymer, Uwe; Ludman, Peter; Danchin, Nicolas; Kala, Petr; Laroche, Cécile; Sadeghi, Masoumeh; Caporale, Roberto; Shaheen, Sameh Mohamed; Legutko, Jacek; Iakobsishvili, Zaza; Alhabib, Khalid F; Motovska, Zuzana; et al.
Abstract: Aims : The aim of this study was to determine the contemporary use of reperfusion therapy in the European Society of Cardiology (ESC) member and affiliated countries and adherence to ESC clinical practice guidelines in patients with ST-elevation myocardial infarction (STEMI). Methods and results : Prospective cohort (EURObservational Research Programme STEMI Registry) of hospitalized STEMI patients with symptom onset <24 h in 196 centres across 29 countries. A total of 11 462 patients were enrolled, for whom primary percutaneous coronary intervention (PCI) (total cohort frequency: 72.2%, country frequency range 0–100%), fibrinolysis (18.8%; 0–100%), and no reperfusion therapy (9.0%; 0–75%) were performed. Corresponding in-hospital mortality rates from any cause were 3.1%, 4.4%, and 14.1% and overall mortality was 4.4% (country range 2.5–5.9%). Achievement of quality indicators for reperfusion was reported for 92.7% (region range 84.8–97.5%) for the performance of reperfusion therapy of all patients with STEMI <12 h and 54.4% (region range 37.1–70.1%) for timely reperfusion. Conclusions : The use of reperfusion therapy for STEMI in the ESC member and affiliated countries was high. Primary PCI was the most frequently used treatment and associated total in-hospital mortality was below 5%. However, there was geographic variation in the use of primary PCI, which was associated with differences in in-hospital mortality. Graphical Abstract: